Single-Phase Shunt Active Power Filter Based on a 5-Level Converter Topology - José Gabriel Oliveira Pinto (Energies, 2018)
This paper presents a single-phase Shunt Active Power Filter (SAPF) with a multilevel converter based on an asymmetric full-bridge topology capable of producing five distinct voltage levels. The calculation of the SAPF compensation current is based on the Generalized Theory of Instantaneous Reactive Power (p-q theory) modified to work in single-phase installations, complemented by a Phase-Locked Loop algorithm and by a dedicated algorithm to regulate the voltages in the DC-link capacitors. The control of the SAPF uses a closed loop predictive current control, followed by a multilevel Sinusoidal Pulse-Width Modulation technique with two vertical distributed carriers, which were specially conceived to deal with the asymmetric nature of the converter legs. Along the paper, some simulation results are used to show the main characteristics of the 5-level converter and control algorithms, and the hardware topology and control algorithms are described in detail. In order to demonstrate the feasibility and performance of the proposed SAPF based on a 5-level converter, a laboratory prototype was developed and experimental results obtained under diverse conditions of operation, with linear and non-linear loads, are presented and discussed in this paper.